Connection between self esteemand attitudes toward family violence in women - Gibson Noyli, Ana Matos (2007)
The present research is a comparative and correlative study; the sample was composed be a universe of 158 women with ages ranging from 18 to 45 years. The instrument used was Ofelia Montes, BS´ Scale of Attitudes toward family violence in  the couple relantionship and Barksdale´ Self- esteem Inventory List. The conclusions of the study carried out show that there are no remarkable differences in the self-esteem relation and attitudes toward family violence. The reason of  this is the common belief, uses and customs that validate and legalize family violence, putting women in an unfair situation by helping to sit up and internalize at an  early age, in the familiar environments  and in the society, the gender – based injustice instead of the healthy ways to cope with their rights.